Properties of native and oxidized corn starch/polystyrene blends under conditions of reactive extrusion using zinc octanoate as a catalyst - Gutiérrez Carmona, Tomy José (2017)
Native and oxidized corn (Zea mays) starch/polystyrene (PS) blends containing glycerol as a plasticizer were prepared by reactive extrusion in a twin-screw extruder using zinc octanoate (Zn(Oct)2) as a catalyst, followed by compression molding. Blends were characterized in terms of their: average molecular weight, moisture content, infrared (FTIR) spectra, water solubility, thermogravimetric (TGA) properties, differential scanning calorimetry (DSC) curves, X-ray diffraction (XDR) patterns, stability in acidic or alkaline medium, and microstructural, mechanical and antimicrobial properties. The results clearly show that the catalyst used produced cross-linking between the starch and PS, and that the oxidative modification of the starch increased its reactivity. This was demonstrated by the increase in molecular weight, thermal resistance, and hydrophobicity of films prepared from the oxidized starch/PS plus catalyst. This increase in hydrophobicity of the starch modified systems was due to the carboxyl and carbonyl groups introduced into the starch structure. As a result, phase separation was more obvious, despite the increase in the cross-linking rate between the oxidized starch and the PS. Finally, none of the films showed signs of swelling or antimicrobial activity. Nonetheless, the catalyst exhibited excellent antimicrobial activity against the pathogenic microorganisms evaluated.